PROSES BERPIKIR SISWA AUTIS DALAM MENYELESAIKAN SOAL KONTEKTUAL MATEMATIKA DILIHAT DARI TEORI SURYABRATA - Setiawani, Susi; Hobri, Hobri; Wibowo, Hendrik Cahyo (Department of Mathematics Education , University of Jember, 2017)
Abstract: The purpose of this research is to descripbe about autistic students’ thinking process in solving contextual problem standards based on Suryabrata teory’. The data by giving test contextual mathematic problem which integers operations subject. Problem given to autistic students of class VIII SMPLB TPA Jember, amounting to four students. Problem given first validated by 2 doses of mathematics education and 1 math teacher SMPLB TPA Jember. . Data analysis can be observed from students’ work sheet. Student’s answers analyzed according to the components of Suryabrata Teory’. Suryabrata teory’ consists of three components which are (1) forming understanding; (2) forming opinion; (3) drawing conclusion. The results of this study is, autistic students tend to meet the second component of the theory Suryabrata. This is directly proportional to the theory that autistic students have exceptional ideas in solving a problem. Autistic students have difficulty in fulfilling the first and third components of the Suryabrata theory. This is directly proportional to the theory that autism students have difficulties in communication Keywords : Thinking Processes, Autistic students, Integers Operations